Moderate introgression in a single individual genome is sufficient to mislead phylogenomic inference of Triplophysa - Zitu Ma; He Gao; Chuanshuai Xie; Da Ji; Yongrui Lu; Haoyu Wang; Yili Cui; Francisco de Menezes Cavalcante Sassi; Dengyue Yuan; Haiping Liu; Luohao Xu (Molecular Phylogenetics and Evolution, 2026)

Combined exposure to wildfire ash and road salts reshapes skin and gut microbiota and reduces fitness in amphibians - Qing Tong; Qiu-ru Fan; Hong-xin Jiang; Yue-liang Pan; Wen-jing Dong; Ming-da Xu; Zhi-wen Luo; Li-yong Cui (Environmental Research, 2026)

Alcohol and high-fat diet aggravate colitis-induced liver injury via glucocorticoid/IL-6-SAA1 axis in mice - Mingrui Zhao; Han Li; Xinghua Gao; Huijuan Da; Xun Cui; Dongquan Jing; Qixiang Zhao; Ying Wang; Yanling Guo; Zhenhua Gao; Shentian Zhuang; Qiuhua Cao (Food and Chemical Toxicology, 2026)

Microbial mechanisms of sulfamethoxazole biodegradation at bio-anode elucidated by integrated metagenomics and stable-isotope probing - Hongli Lu; Hui Lin; Da Kang; Donglin Wang; Qiaojuan Wang; Jie Mao; Dan Cui; Yaohui Bai; Jiuhui Qu; Yongzhen Peng (Chemical Engineering Journal, 2026)

Recovery trajectories of amphibian skin microbiota following ash exposure across translocation and natural recovery scenarios - Qing Tong; Qiu-ru Fan; Hong-xin Jiang; Ming-da Xu; Yue-liang Pan; Li-yong Cui (Environmental Pollution, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

Correction: MdSOS2L1 phosphorylates MdVHA-B1 to modulate malate accumulation in response to salinity in apple - Da-Gang Hu; Cui-Hui Sun; Mei-Hong Sun; Yu-Jin Hao (Plant Cell Reports, 2026)

Numerical modeling of freak waves and prediction research based on feature fusion parallel neural networks - Geng-Kun Wu; Yu-Bing Li; Da-Wei Li; Chao Cui (Ocean Engineering, 2026)

Endothelial FAM171A2 is required for maintaining autophagy flux and blood–brain barrier integrity - Si-Da Han; Ning Ding; Jia-hui Huang; Yi-Wei Feng; Kai-Min Wu; Shi-Dong Chen; Qiang Dong; Mei Cui; Ting-ting Wang; Peng Yuan; Jin-Tai Yu (Science Bulletin, 2026)

Experimental investigation of pile anchors in sand under inclined cyclic loading for TLP supported floating offshore wind turbines - Jianbin Cui; Youhu Zhang; Shuzhao Li; Da Li; Ying Huang; Guodong Sun (Ocean Engineering, 2026)

Reaction mechanisms and catalyst design principles of MOFs and their derivatives in the electrocatalytic nitrate reduction for ammonia production - Huaiyu Zhou; Qing Wang; Yan Pan; Shuo Pan; Da Cui; Jingru Bai (Journal of Environmental Chemical Engineering, 2026)

Optimizing hydrogenation activation pathway in Cu-based hierarchical microspheres for sustainable nitrophenols hydrogenation with ultralow-reductant-consumption - Fengting Geng; Jiajia Cheng; Xuexin Niu; Xiaoli Wang; Hongxing Wang; Chaoyue Zhao; Ling Wang; Yong-Zheng Zhang; Da-Shuai Zhang; Xiuling Zhang; Lifeng Cui; Longlong Geng (Chemical Engineering Journal, 2026)

A core-shell fiber membrane with synergistic radiative cooling and thermal buffering for all-weather personal comfort - Xiaohong Wu; Akbar Bashir; Chak-Yin Tang; Gary Chi-Pong Tsui; Ziqi Li; Nanhao Chen; Yichi Zhang; Yan Chen; Jie Cui; Juncheng Zhuang; Chen Liu; Yuanyuan Li; et al. (Chemical Engineering Journal, 2026)

TMEM158-mediated TGF-β signaling pathway modulates the sensitivity of TP53-deficient osteosarcoma to USP14 inhibitors - Zi-Yu Chen; Miersalijiang Yasen; Song-Yao Jiang; Zi-Yi Ye; Qin-Xin Yang; Cui-Ni Lu; Yi Shi; Xin-Yun Liu; Ting-Ting Du; Xiao-Mei Tang; Da Fu; Yu-Shui Ma; et al. (Molecular and Cellular Biochemistry, 2026)

Fatigue behavior and remaining life evaluation of cracked rib-to-deck joints reinforced with inverted U-shaped plates - Ming-zhe Li; Chuang Cui; Qing-hua Zhang; Le-tian Da; Zhen-yu Cheng; Chuan Wei; Feng-kun Cui; Ying-fang Yang (Engineering Structures, 2026)

Multi-objective optimization study of wave elimination and electricity generation performance of Savonius hydrokinetic turbine array based on metamodel - Ruiyin Song; Haihan Yu; Congjie Ren; Xi Cui; Fengshen Li; Lei Zhang; Gao Bai; Kai Chen; Da Liu (Ocean Engineering, 2026)

Occurrence, distribution, and risk assessment of antibiotics in post-harvest and drained ponds of Sheyang River estuary in Jiangsu Province: Implications for sustainable aquaculture management - Wenqian Shan; Shiya Gu; Wangrong Cui; Xinyun Feng; Xin Song; Jianwei Dong; Hui Xie; Da Li (Journal of Contaminant Hydrology, 2026)

Numerical investigation of the screen mesh effects on the heat transfer performance of wick structured heat pipe - Youyuan Fu; Da Chen; Yuxuan Cui; Shang Mao; Zilong Deng (Annals of Nuclear Energy, 2025)

Hydrogen production from supercritical water gasification of corn stalk with reactive co-solvents: Regulator roles of free radicals - Da Cui; Xuelong Sui; Yuqi Wang; Hon Man Luk; Shuang Wu; Chunlei Wu; Jinghui Zhang; Qiuyun Lu; Qing Wang; Xuehua Zhang (Chemical Engineering Journal, 2025)

Recent advances in non-precious metal electrocatalysts for anion exchange membrane water electrolysis: Mechanistic insights, catalyst design, and structural regulation strategies - Qing Wang; Yuan Wang; Hon Man Luk; Jihui Tang; Shuang Wu; Dongyang Wu; Zhongyuan Hu; Da Cui; Jinghui Zhang (Chemical Engineering Journal, 2025)

Model Construction and Research of Synergistic Effect Mechanism on Subglacial Bedrock Core Breaking - Rusheng Wang; Zhihao Cui; Guigang Tu; Xiaopeng Fan; Da Gong; Siqi Hong; Xinyu Lv (Rock Mechanics and Rock Engineering, 2025)

Reducing toxicity of atrazine using subcritical hydrolysis technology and investigation the hydrolysis mechanism - Shuo Pan; Huaiyu Zhou; Shuang Wu; Qing Wang; Jingru Bai; Da Cui; Junting Su (Environmental Science and Pollution Research, 2025)

Insight into the effect of manganese oxidation state on the synthesis of ethylene urea from CO2 and ethylenediamine - Fei Wang; Biao Da; Yulong Jin; Piracha Sanwal; Lei Cui; Siru Chen; Jie Xu; Bing Xue; Gao Li (Journal of Environmental Sciences, 2025)

Genome-wide association analysis provides genetic insights into variation of nutritional quality traits in sea cucumber Apostichopus japonicus - Hongyuan Zhao; Da Huo; Wei Cui; Chunxi Jiang; Shilin Liu; Irène Rasoamananto; Libin Zhang; Lina Sun (Journal of Oceanology and Limnology, 2025)

Accuracy evaluation of load distribution in engineering vehicles under extreme environments - Guohua Wu; Xuefei Li; Zongwei Yao; Da Cui; Wei Guan; Zi Wang; Hewen Zheng; Yongpeng Wang (Journal of Cleaner Production, 2025)

Enhanced nonradical oxidation of thiocyanate by nano γ-Fe2O3 and Fe3C-modified 2D hierarchical porous carbon nanosheets - Yang Yang; Jianshe Chen; Daxue Fu; Yongfeng Chang; Kuiren Liu; Shuang Cui; Yina Li; Binchuan Li; Shicheng Wei; Da Li; Qing Han (Journal of Environmental Chemical Engineering, 2025)

Synergistic toxicity of cadmium and triadimefon on the microbiota and health of Rana dybowskii tadpoles - Xiao-yun Han; Peng Guo; Qiu-ru Fan; Qing-bo Zhou; Ming-da Xu; Xin-zhou Long; Li-yong Cui; Qing Tong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Differential impact of wildfire and rice straw ash on the skin microbiota of Rana dybowskii adults and tadpoles - Xin-zhou Long; Ming-da Xu; Wen-jing Dong; Xiu-mei Yang; Li-yong Cui; Qing Tong (Environmental Pollution, 2025)

Dual role of multistage inoculation in manipulating bacterial community assembly patterns to improve degradation of lignocellulose during rice or corn straw composting - Da Liu; Ziwei Jiang; Wenxuan Feng; Yufeng Zhao; Pengfei Tang; Jizhe Cui; Zhan Zhao; Qian Lu (Chemical Engineering Journal, 2025)

Influence of wildfire ash concentration on development, survival, and skin and gut microbiota of Rana dybowskii - Qing Tong; Ming-da Xu; Wen-jing Dong; Xin-zhou Long; Xiao-yun Han; Li-yong Cui (Science of The Total Environment, 2025)

ZnCur nanoparticle-enhanced multifunctional hydrogel platform: Synergistic antibacterial and immunoregulatory effects for infected diabetic wound healing - Yan-Wen Ding; Zhi-Wei Zhang; Xin-Yu Cui; Rui-Yang Hu; Yang Li; Si-Da Huang; Si-Qi Du; Jin-Wei Dao; Dai-Xu Wei (Chemical Engineering Journal, 2025)

Dedolomitization arises the knife-like structure of dolostone: insights from the oolitic dolostone of Cambrian Zhangxia formation, North China Craton - Zhe-Xin Cai; Shan-Shan Li; Yi-Ning He; Tao Cui; Xin-Yu Wu; Hao-Cheng Yu; Zhao-Liang Hou; Yu-Tian Tao; Da Wang; Kun-Feng Qiu (Carbonates and Evaporites, 2024)

Towards sustainable fruit production: Identifying challenges and optimization strategies - Liangquan Wu; Xiaojun Yan; Jiayi Huang; Xiuzhu Xu; Siwen Zhang; Shilei Cui; Xiaohui Chen; Zhixiong Zeng; Shuangyong Huang; Yingzhe Zeng; Yibin Weng; Bingkun Lu; et al. (Agricultural Systems, 2024)

A Kriging-based method for calibrating the bonded-particle model parameters of iron ore - Haoyan Zhang; Shuai Wang; Yang An; Yukuan Wang; Shuwei Wu; Da Cui; Guoqiang Wang (Minerals Engineering, 2024)

Cyanide content, nutrient composition, physicochemical properties and sensory quality of flaxseed oil bodies prepared from flaxseeds (Linum usitatissimum L.) treated with different heat treatment methods - Rui Zheng; Hui-Lin Liu; Nan-Nan Cui; Jun-Zhuo Zhou; Xin Sun; Fa-Wen Yin; Da-Yong Zhou (Food Research International, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Integrating L-cysteine coated polydopamine nanoparticles and deep eutectic solvents into chitosan matrix for multifunctional food packaging application - Ying Mao; Malin Cui; Xiaoyan Zhang; Hetong Lin; Da-Peng Yang (Chemical Engineering Journal, 2024)

Immune checkpoint-regulatable hydrogel-immobilized nanotherapeutics for post-surgical treatment of osteosarcoma - Da-Wang Zhao; Zhiliang Gao; Meng Si; Rui Hu; Xue Ma; Kaiwen Liu; Yixiang Zhao; Qiting He; Xiangzhen Kong; Chunwang Jia; Haoxin Zhai; Yuanqiang Zhang; et al. (Chemical Engineering Journal, 2024)

Bonding-slip behaviour of steel-concrete interfaces in CFDST members with PBL ribs - Yan-Li Shi; Jia-Xing Ren; Jia-Hao Fan; Wen-Da Wang; Hai-Cui Wang (Engineering Structures, 2024)

Impact of wildfire ash on skin and gut microbiomes and survival of Rana dybowskii - Ming-da Xu; Wen-jing Dong; Xin-zhou Long; Xue-wen Yang; Xiao-yun Han; Li-yong Cui; Qing Tong (Journal of Hazardous Materials, 2024)

Status and trends in the stability of the three largest ice shelves in Antarctica - Rongxing Li; Guojun Li; Lu An; Menglian Xia; Da Lv; Yuan Cheng; Aiguo Zhao; Tian Chang; Xiangbin Cui; Shengkai Zhang; Shijie Liu; Yixiang Tian; et al. (Science China Earth Sciences, 2024)

Impact of antibiotic therapy on cutaneous and gut microbiota in Rana dybowskii amphibians: Insights and implications - Xin-zhou Long; Wen-jing Dong; Ming-da Xu; Xue-dong Han; Xiao-yun Han; Li-yong Cui; Qing Tong (Aquaculture, 2024)

Assessment of co-benefits from on-road vehicle electrification in Suzhou City, China - Feiyue Qian; Cui Da; Chunchen Lu; Xinyu Gu; Junjian Yang; Chaowei Shi; Zhen Feng; Yuanyuan Cheng (Urban Climate, 2024)

The A subunit of vacuolar H+-ATPase gene (CmVHA-A) plays opposite roles in plant growth and drought tolerance of chrysanthemum under different growing conditions - Yan-Hong Liu; Zhen-Hao Zou; Man-Man Zhang; Zhang-Ji Guan; Lian-Da Du; Da-Gang Hu; Cheng-Shu Zheng; Cui-Hui Sun (Plant Science, 2024)

Developmental exposure to the Fox River PCB mixture modulates behavior in juvenile mice - Rebecca J. Wilson; Youjun P. Suh; Ilknur Dursun; Xueshu Li; Felipe da Costa Souza; Ana Cristina Grodzki; Julia Y. Cui; Hans-Joachim Lehmler; Pamela J. Lein (NeuroToxicology, 2024)

Newly graphene/polypyrrole (rGO/PPy) modified carbon felt as bio-cathode in bio-electrochemical systems (BESs) achieving complete denitrification - Yue-Jia Yang; Shuai Wang; Da Kang; Xin Lu; Zi-Chang Lu; Zhuo-Chao Liu; Li-Ming Yang; Dan Cui (Environmental Research, 2024)

A comprehensive evaluation of lipid profiles and nutritional quality in different animal source muscle tissues - Shuang Cui; Ying Wang; Zheng Zhou; Yu-Ying Zhang; Xu-Hui Huang; Da-Yong Zhou; Lei Qin (Food Bioscience, 2024)

Antiproliferative polycyclic polyprenylated acylphloroglucinols from Garcinia paucinervis - Cui-Cui Jia; Jing-Jing Xue; Zhan-Lin Li; Da-Hong Li; Hui-Ming Hua (Natural Product Research, 2024)

Rice straw ash and amphibian health: A deep dive into microbiota changes and potential ecological consequences - Wen-jing Dong; Ming-da Xu; Xue-wen Yang; Xiu-mei Yang; Xin-zhou Long; Xiao-yun Han; Li-yong Cui; Qing Tong (Science of The Total Environment, 2024)

Revealing new insights: Two-center evidence of microplastics in human vitreous humor and their implications for ocular health - Yizhou Zhong; Yuhang Yang; Linan Zhang; Dahui Ma; Kailiang Wen; Jiachun Cai; Zhanmou Cai; Cui Wang; Xiaoyan Chai; Jingwen Zhong; Boxuan Liang; Yuji Huang; et al. (Science of The Total Environment, 2024)

Analysis of fuel properties of hydrochar derived from food waste and biomass: Evaluating varied mixing techniques pre/post-hydrothermal carbonization - Shuang Wu; Qing Wang; Da Cui; Xinmin Wang; Dongyang Wu; Jingru Bai; Faxing Xu; Zhenye Wang; Jinghui Zhang (Journal of Cleaner Production, 2023)

Enhancing ocean environment prediction in Yellow Sea through targeted observation using ocean acoustic tomography - Cui Baolong; Liu Jingyi; Guo Wuhong; Da Lianglong (Frontiers in Marine Science, 2023)
Ocean Acoustic Tomography (OAT) is an efficient and economical marine acoustic observation technique. Targeted observation is an appealing procedure to reduce the uncertainty of ocean environment prediction through additional observation. This study aimed to assess the validity of OAT as an observation method for targeted observation. OAT based on Niche Genetic Algorithm was employed to extract sound speed and temperature profiles from acoustic transmission time, utilizing data from the 2019 Yellow Sea experiment. The inversion results were compared with measurement data, which are found to be accurate and reliable. To further evaluate OAT as targeted observation method, the vertical bias structure of OAT was added on synchronous measurement data in the sensitive area of targeted observation to simulate OAT observation in sensitive area. This simulated data was then incorporated into a 3D-Var assimilation system to improve the short-term prediction of the target region. Comparing the predictions derived with the measurement data at the verification time, it shows that the simulated OAT observation improved the quality of target region prediction, indicating that OAT can be an effective observation method for targeted observation. An Observing System Simulation Experiment was conducted to assess the impact of OAT characteristics on prediction improvement. The results show that both adding observation nodes and extending the observation duration have positive effects, while extending the observation duration performs better.

Hydrothermal carbonization of food waste for sustainable biofuel production: Advancements, challenges, and future prospects - Shuang Wu; Qing Wang; Minghui Fang; Dongyang Wu; Da Cui; Shuo Pan; Jingru Bai; Faxing Xu; Zhenye Wang (Science of The Total Environment, 2023)

Synthesis of flower-shaped cyclodextrin microporous organic networks for selective recovery of acetophenone and 1-phenylethanol from petrochemical effluents - Yun-Da Yue; Yu Gao; Shi-Ya Fu; Yuan-Yuan Cui; Cheng-Xiong Yang (Chemical Engineering Journal, 2023)

Electron uptake from solid electrodes promotes the more efficient conversion of CO2 to polyhydroxybutyrate by using Rhodobacter sphaeroides - Shuwei Li; Minsoo Kim; Da Seul Kong; Kyoungseon Min; Guangxi Wu; Meiying Cui; Changman Kim; You-Kwan Oh; Soek Kim; Soo Youn Lee; Sung Gyun Kang; Yvonne Nygård; et al. (Chemical Engineering Journal, 2023)

Mass balance of the Antarctic Ice Sheet from 2013 to 2018 estimated using the input-output method with updated remote sensing products - Yuan Cheng; Gang Hai; Xiangbin Cui; Da Lv; Gang Qiao; Rongxing Li (Science China Earth Sciences, 2023)

Recent advances in luminescence and aptamer sensors based analytical determination, adsorptive removal, degradation of the tetracycline antibiotics, an overview and outlook - Ma-Lin Cui; Zi-Xuan Lin; Qing-Fan Xie; Xiao-Yan Zhang; Bing-Qing Wang; Miao-Ling Huang; Da-Peng Yang (Food Chemistry, 2023)

N-Fluorobenzenesulfonimide as a multifunctional electrolyte additive for co-stabilizing dual-electrodes of lithium metal batteries with enhanced electrochemical performance - Xianjun Weng; Yanyang Qin; Xinyu Da; Yuanjun Zhao; Xuetian Deng; Bo Wen; Manying Cui; Xiangkai Yin; Yaqiong Su; Jiangxuan Song; Shujiang Ding; Xiaofei Hu; et al. (Chemical Engineering Journal, 2023)

A comprehensive health effects assessment of the use of sanitizers and disinfectants during COVID-19 pandemic: a global survey - Fallah Hashemi; Lori Hoepner; Farahnaz Soleimani Hamidinejad; Daniela Haluza; Sima Afrashteh; Alireza Abbasi; Elma Omeragić; Belma Imamović; Narin A. Rasheed; Taqi M. J. Taher; Fitri Kurniasari; Dhuha Youssef Wazqar; et al. (Environmental Science and Pollution Research, 2023)

Hybrid bioreactor built-in with fixed bio-carriers for denitrification with low C/N ratio: Hydrodynamic optimization and microbial divergence - Ke-Wen Wang; Wen-Zong Liu; Da Kang; Yu-Xiang Zhang; Dan Cui (Environmental Research, 2023)

Laminar burning characteristics of bio-aviation fuel candidate derived from lignocellulosic biomass - Cangsu Xu; Kai Liu; Yang Song; Da Cui; Xiaolu Li; Qiyang Wang; Francis Oppong (Fuel, 2023)

Constructing robust cathode/Li interfaces and intensifying ion transport kinetics for PEO-based solid-state lithium-sulfur batteries - Jin Li; Haitao Zhang; Yingyue Cui; Haoran Da; Hui Wu; Yingjun Cai; Suojiang Zhang (Chemical Engineering Journal, 2023)

Greenhouse gas emission benefits of adopting new energy vehicles in Suzhou City, China: A case study - Cui Da; Xinyu Gu; Chunchen Lu; Ruiqi Hua; Xinyue Chang; Yuanyuan Cheng; Feiyue Qian; Yiheng Wang (Environmental Science and Pollution Research, 2022)

Different Surface Appearances Caused by Unbalanced Mn2+ Accumulation in Gallstones Consisting of Cholesterol and CaCO3 Obtained from a Patient After Cholecystectomy - Da-Yong Lu; Jin Zhang; Qiao-Li Liu; Hong-Guang Wang; Meng Cui (Biological Trace Element Research, 2022)

Electrokinetic stabilization of marine clayey soil using magnesium chloride solution: A green soil stabilizer - Yongqiang Tang; Ningwei Wang; Feng Xu; Da Teng; Xiaoming Cui (Marine Georesources & Geotechnology, 2022)

Rapid visual detection of porcine reproductive and respiratory syndrome virus via recombinase polymerase amplification combined with a lateral flow dipstick - Xiao-Xiao Tian; Tao Wang; Xing-Yang Cui; Xin-Yi Huang; Yue Sun; Da-Song Xia; Yong-Bo Yang; Xue-Hui Cai; Tong-Qing An (Archives of Virology, 2022)

Safety evaluation and ibuprofen removal via an Alternanthera philoxeroides-based biochar - Yuan-da Du; Xin-qian Zhang; Li Shu; Yu Feng; Cui Lv; Hong-qiang Liu; Fei Xu; Qian Wang; Cong-cong Zhao; Qiang Kong (Environmental Science and Pollution Research, 2021)

Identification of the sensitive area for targeted observation to improve vertical thermal structure prediction in summer in the Yellow Sea - Huiqin Hu; Jingyi Liu; Lianglong Da; Wuhong Guo; Kun Liu; Baolong Cui (Acta Oceanologica Sinica, 2021)

Dynamic process analysis of the Niumiangou landslide triggered by the Wenchuan earthquake using the finite difference method and a modified discontinuous deformation analysis - Da Huang; Qiu-jie Meng; Yi-xiang Song; Sheng-hua Cui; Duo-feng Cen (Journal of Mountain Science, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

Identification and full-genome sequencing of canine kobuvirus in canine fecal samples collected from Anhui Province, eastern China - Yong Wang; Yongqiu Cui; Yeqiu Li; Xiaopeng Wang; Kankan Yang; Da Zhang; Liang Zhao; Caixia Bai; Shudong Jiang; Yongdong Li (Archives of Virology, 2020)

Systemic effect of dietary lipid levels and α-lipoic acid supplementation on nutritional metabolism in zebrafish (Danio rerio): focusing on the transcriptional level - Chen-cui Huang; Jian Sun; Hong Ji; Gen Kaneko; Xing-da Xie; Zhi-guang Chang; Wei Deng (Fish Physiology and Biochemistry, 2020)

Dynamics of radial oxygen loss in mangroves subjected to waterlogging - Hao Cheng; Mei-Lin Wu; Chang-Da Li; Fu-Lin Sun; Cui-Ci Sun; You-Shao Wang (Ecotoxicology, 2020)

Detailed Analysis of Lipids in Edible Viscera and Muscles of Cooked Crabs Portunus trituberculatus and Portunus pelagicus - Ting Lu; Yan Shen; Guo-Xin Cui; Fa-Wen Yin; Zhuo-Liang Yu; Da-Yong Zhou (Journal of Aquatic Food Product Technology, 2020)

Tissue-Specific Monoallelic Expression of Bovine AXL is Associated with DNA Methylation of Promoter DMR - Da Xu; Guannan Wang; Junliang Li; Cui Zhang; Weina Chen; Dongjie Li; Shijie Li (Biochemical Genetics, 2019)

Choline, not folate, can attenuate the teratogenic effects ofdibutyl phthalate (DBP) during early chick embryo development - Rui Wang; Da-Guang Sun; Ge Song; Chun Yi Guan; Yi Cui; Xu Ma; Hong-Fei Xia (Environmental Science and Pollution Research, 2019)

GIS-Supported Airfield Selection near Zhongshan Station, East Antarctica, based on Multi-Mission Remote Sensing Data - Xiangbin Cui; Jiaxin Liu; Yixiang Tian; Bo Sun; Rongxing Li; Alexey Markov; Da Lv; Gang Hai; Gang Qiao; Tiantian Feng (Marine Geodesy, 2019)

LINC24065 is a monoallelically expressed long intergenic noncoding RNA located in the cattle DLK1–DIO3 cluster - Cui Zhang; Da Xu; Weina Chen; Junliang Li; Qinghua Gao; Shijie Li (Journal of Genetics, 2019)

Impacts of Land Cover Changes on Ecosystem Carbon Stocks Over the Transboundary Tumen River Basin in Northeast Asia - Hengxing Xiang; Mingming Jia; Zongming Wang; Lin Li; Dehua Mao; Da Zhang; Guishan Cui; Weihong Zhu (Chinese Geographical Science, 2018)

Polymorphic Imprinting of SLC38A4 Gene in Bovine Placenta - Da Xu; Cui Zhang; Junliang Li; Guannan Wang; Weina Chen; Dongjie Li; Shijie Li (Biochemical Genetics, 2018)

HpaP, a novel regulatory protein with ATPase and phosphatase activity, contributes to full virulence in Xanthomonas campestris pv. campestris - Ping Cui; Rui‐Fang Li; Da‐Pei Zhang; Ji‐Liang Tang; Guang‐Tao Lu (Environmental Microbiology, 2018)
Summary The ability of the bacterial phytopathogen Xanthomonas campestris pv. campestris ( Xcc ) to cause disease is dependent on the type III secretion system (T3SS). Proteins of the Xcc T3SS are encoded by hrp (hypersensitive response and pathogenicity) genes and whose expression is mainly controlled by the regulators HrpG and HrpX. Here, we describe the identification and characterization of a previously unknown regulatory protein ( named HpaP), which plays important role in hrp gene expression and virulence in Xcc . Clean deletion of hpaP demonstrated reduced virulence and HR (hypersensitive response) induction of Xcc and alterations in cell motility and stress tolerance. Global transcriptome analyses revealed that most hrp genes were down regulated in the hpaP mutant, suggesting HpaP positively regulates hrp genes. GUS activity assays implied that HpaP regulates the expression of hrp genes via controlling the expression of hrpX . Biochemical analyses revealed that HpaP protein had both ATPase and phosphatase activity. While further site‐directed mutagenesis of conserved residues in the PTP loop (a protein tyrosine phosphatase signature) of HpaP resulted in the loss of both phosphatase activity and regulatory activity in virulence and HR. Taken together, the findings identify a new regulatory protein that controls hrp gene expression and virulence in Xcc .

New phenanthrene and 9, 10-dihydrophenanthrene derivatives from the stems of Dendrobium officinale with their cytotoxic activities - Gui-Yun Zhao; Bo-Wen Deng; Chong-Yu Zhang; Yi-Da Cui; Jia-Yi Bi; Guo-Gang Zhang (Journal of Natural Medicines, 2018)

Cryopreservation of grapevine (Vitis spp.)—a review - Wen-Lu Bi; Chen Pan; Xin-Yi Hao; Zhen-Hua Cui; Mafatlal M. Kher; Zvjezdana Marković; Qiao-Chun Wang; Jaime A. Teixeira da Silva (In Vitro Cellular & Developmental Biology - Plant, 2017)

A statistical analysis of hourly heavy rainfall events over the Beijing metropolitan region during the warm seasons of 2007–2014 - Huiqi Li; Xiaopeng Cui; Da‐Lin Zhang (International Journal of Climatology, 2017)
A statistical analysis of the spatiotemporal characteristics of hourly heavy rainfall ( HHR ) events and rainstorm days, defined as greater than 20 mm h −1 and 50 mm day −1 , respectively, is performed using observations at 5‐min intervals from 155 automated weather stations ( AWSs ) over the Beijing metropolitan region ( BMR ) during the warm seasons of 2007–2014. Results show pronounced variability in the frequencies and rainfall amounts of both HHR events and rainstorm days across the BMR of less than 150 km width from the west to east. That is, higher‐ (lower) frequency HHR events with more (less) accumulated rainfall amounts take place in eastern Haidian and over the BMR 's northeast mountains (west and northwest mountains). Many extreme rainfall and even record‐breaking events, in terms of the frequency, duration, rainfall amount and intensity, are found to occur in the regions of high‐frequency HHR events and rainstorm days. The frequency of rainstorm days with HHR events accounts for more than 50% of that of total rainstorm days over the BMR 's plains and near the northeast mountains. Results also show that HHR events occur most frequently in late July, and typically peak during 1600–2000 LST . A comparison of the averaged surface meteorological variables and upper‐air sounding at 0800 LST between HHR and non‐ HHR days reveals that the occurrences of the HHR events coincide with the distribution of surface warmer and more humid air as well as organized convergence in the presence of an unstable environment with surface south‐ to southeasterly winds, low‐level south to southwesterly flows and a deep layer of higher moisture content. These results suggest likely the positive influences of urban environment and mountain‐plain circulations on the generation of the HHR events, given favourable larger‐scale conditions.

Alismol, a Sesquiterpenoid Isolated from Vladimiria souliei, Suppresses Proinflammatory Mediators in Lipopolysaccharide-Stimulated Microglia - Dongdong Shi; Xiaoqiang Song; Yuanqiang Guo; Jing Xu; Yu Liu; Jingling Zhang; Chun-Ai Cui; Da-Qing Jin (Journal of Molecular Neuroscience, 2017)

Dissipation of excess excitation energy of the needle leaves in Pinus trees during cold winters - AO Zhang; Zhen-Hai Cui; Jia-Lin Yu; Zi-Ling Hu; Rui Ding; Da-Ming Ren; Li-Jun Zhang (International Journal of Biometeorology, 2016)

Highly selective and efficient biotransformation of linarin to produce tilianin by naringinase - Pan Cui; Tong-Yi Dou; Shi-Yang Li; Jun-Xia Lu; Li-Wei Zou; Ping Wang; Yan-Ping Sun; Da-Cheng Hao; Guang-Bo Ge (Biotechnology Letters, 2016)

MdSOS2L1 phosphorylates MdVHA-B1 to modulate malate accumulation in response to salinity in apple - Da-Gang Hu; Cui-Hui Sun; Mei-Hong Sun; Yu-Jin Hao (Plant Cell Reports, 2016)

Characteristics Analyses and Comparisons of the Protein Structure Networks Constructed by Different Methods - Shangli Cheng; Hua-Lin Fu; Da-Xiang Cui (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Retraction Note to: Genetic variations in the KIR gene family may contribute to susceptibility to ankylosing spondylitis: a meta-analysis - Hai-Ning Zuo; Zhi-Long Wang; Dao-Ran Cui; Da-Jiang Xin (Molecular Biology Reports, 2015)

A Potent Multi-functional Neuroprotective Derivative of Tetramethylpyrazine - Hai-Yun Chen; Da-Ping Xu; Guo-Lian Tan; Wei Cai; Gao-Xiao Zhang; Wei Cui; Jin-Zhao Wang; Cheng Long; Ye-Wei Sun; Pei Yu; Karl Wahkeung Tsim; Zai-Jun Zhang; et al. (Journal of Molecular Neuroscience, 2015)

Relationship between haze and acute cardiovascular, cerebrovascular, and respiratory diseases in Beijing - Jin-jun Zhang; Meng-meng Cui; Da Fan; De-shan Zhang; Hui-xin Lian; Zhao-yin Yin; Jin Li (Environmental Science and Pollution Research, 2015)

Three-dimensional tensor controlled-source electromagnetic modeling based on the vector finite-element method - Ying-Cai Hu; Tong-Lin Li; Cui-Song Fan; Da-Yong Wang; Jian-Ping Li (Applied Geophysics, 2015)

EGFR-AKT-mTOR activation mediates epiregulin-induced pleiotropic functions in cultured osteoblasts - Jian-bo Fan; Wei Liu; Xin-hui Zhu; Kun Yuan; Da-wei Xu; Jia-jia Chen; Zhi-ming Cui (Molecular and Cellular Biochemistry, 2015)

RETRACTED ARTICLE: Genetic variations in the KIR gene family may contribute to susceptibility to ankylosing spondylitis: a meta-analysis - Hai-Ning Zuo; Zhi-Long Wang; Dao-Ran Cui; Da-Jiang Xin (Molecular Biology Reports, 2014)

Complete genome sequence analysis identifies a new genotype of brassica yellows virus that infects cabbage and radish in China - Xiao-Yan Zhang; Hai-Ying Xiang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2014)

Influence of dip directions on the main deformation region of layered rock around tunnels - Zhen-dong Cui; Da-an Liu; Fa-quan Wu (Bulletin of Engineering Geology and the Environment, 2014)

Coal-burning endemic fluorosis is associated with reduced activity in antioxidative enzymes and Cu/Zn-SOD gene expression - Qi Wang; Kang-ping Cui; Yuan-yuan Xu; Yan-ling Gao; Jing Zhao; Da-sheng Li; Xiao-lei Li; Hou-jin Huang (Environmental Geochemistry and Health, 2014)

Socio-demographic and clinical characteristics of heavy and non-heavy smokers among schizophrenia inpatients in a Chinese Han population - Xiang Yang Zhang; Da Chun Chen; Yun Long Tan; Mei Hong Xiu; Jingyi Cui; Li Hui; Fu De Yang; Thomas R Kosten (Psychopharmacology, 2014)

Expression of OsMSR3 in Arabidopsis enhances tolerance to cadmium stress - Yanchun Cui; Guoyun Xu; Manling Wang; Yan Yu; Mingjuan Li; Pedro S. C. Ferreira da Rocha; Xinjie Xia (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Prevalence of type-specific human papillomavirus and pap results in Chinese women: a multi-center, population-based cross-sectional study - En-Qi Wu; Bin Liu; Jian-Feng Cui; Wen Chen; Jian-Bing Wang; Liang Lu; Mayineur Niyazi; Chao Zhao; Sheng-Da Ren; Chang-Qing Li; Xiang-Zhen Gong; Jennifer S. Smith; et al. (Cancer Causes & Control, 2013)

Effect of sinomenine on vascular smooth muscle cell dedifferentiation and neointima formation after vascular injury in mice - Lihua Zhu; Yarong Hao; Hongjing Guan; Changping Cui; Song Tian; Da Yang; Xinan Wang; Shuming Zhang; Lang Wang; Hong Jiang (Molecular and Cellular Biochemistry, 2013)

Nucleotide sequence of a chickpea chlorotic stunt virus relative that infects pea and faba bean in China - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

Molecular characterization of two genotypes of a new polerovirus infecting brassicas in China - Hai-Ying Xiang; Shu-Wei Dong; Qiao-Xia Shang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2011)

A novel strain of Beet western yellows virus infecting sugar beet with two distinct genotypes differing in the 5′-terminal half of genome - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Virus Genes, 2011)

Marinobacter zhanjiangensis sp. nov., a marine bacterium isolated from sea water of a tidal flat of the South China Sea - Da-Chun Zhuang; Yi-Guang Chen; Yu-Qin Zhang; Shu-Kun Tang; Xiao-Lei Wu; Zhou-Cai Tan; Wen-Jun Li; Xiao-Long Cui (Antonie van Leeuwenhoek, 2009)

Formation of archegonium chamber is associated with nucellar-cell programmed cell death in Ginkgo biloba - Da-Hui Li; Xiong Yang; Ke-Ming Cui (Protoplasma, 2007)

Characterization of a cDNA coding for an extracellular calmodulin-binding protein from suspension-cultured cells of Angelica dahurica - Guo-Hong Mao; Li-Xia Hou; Cun-Bao Ding; Su-Juan Cui; Da-Ye Sun (Planta, 2005)